Mosaic Organization of Orthologous Sequences in Grass Genomes - Song, Rentao; Llaca, Victor; Messing, Joachim (Genome Research, 2002)
Although comparative genetic mapping studies show extensive genome conservation among grasses, recent data provide many exceptions to gene collinearity at the DNA sequence level. Rice, sorghum, and maize are closely related grass species, once sharing a common ancestor. Because they diverged at different times during evolution, they provide an excellent model to investigate sequence divergence. We isolated, sequenced, and compared orthologous regions from two rice subspecies, sorghum, and maize to investigate the nature of their sequence differences. This study represents the most extensive sequence comparison among grasses, including the largest contiguous genomic sequences from sorghum (425 kb) and maize (435 kb) to date. Our results reveal a mosaic organization of the orthologous regions, with conserved sequences interspersed with nonconserved sequences. Gene amplification, gene movement, and retrotransposition account for the majority of the nonconserved sequences. Our analysis also shows that gene amplification is frequently linked with gene movement. Analyzing an additional 2.9 Mb of genomic sequence from rice not only corroborates our observations, but also suggests that a significant portion of grass genomes may consist of paralogous sequences derived from gene amplification. We propose that sequence divergence started from hotspots along chromosomes and expanded by accumulating small-scale genomic changes during evolution.[GenBank Accession Numbers: Rice (Oryza sativa L. ssp. japonica)php200725 region: AF119222; rice (Oryza sativa L. ssp. indica) php200725 region: AF128457; sorghum (Sorghum bicolor) php200725 region: AF114171,AF527807, AF727808, AF527809; maize (Zea mays)php200725 region: AF090447, AF528565; rice chromosome 10 region (2.9 Mb): AC073391, AC087549, AC027657, AC087547, AC027658,AC087546, AC027659, AC087550, AC025905, AC087545, AF229187, AC027660,AC087544, AC027661, AC027662, AC087543, AC073392, AC087542, AC025906,AC073393, AC025907.]
10.1101/gr.268302